The Potential of Bilimbi Leaves (Averrhoa bilimbi Linn.) Extract as Irrigation Solution to Remove Smear Layer in Dental Root Canal: An Invitro Study - Windy Fanika Putri; Steven Wijaya; Dian Soraya Tanjung (HM Publisher, 2022)
Background: Root canal treatment is performed to eliminate the infection in the pulp tissue. One of the critical steps in root canal treatment is irrigation, which aims to clean debris and smear layer. This study aims to compare the effectiveness of star fruit extract (Averrhoa bilimbi Linn) at concentrations of 5%, 10%, 15%, and 20% with EDTA 17% in cleaning the smear layer on the one-third of apical root canals. Methods: This type of research is an experimental in vitro laboratory with a post-test only control group design. The sample of this study consisted of 25 premolars which were randomly divided into five groups. The teeth were instrumented with a K-file and irrigated with the following materials: groups I, II, III, and IV using bilimbi leaves extract, each with concentrations of 5%, 10%, 15%, and 20% and group V (positive control). ) using 17% EDTA. SEM (scanning electron microscope) was used to measure the cleanliness score of the smear layer on the apical third of the root canal. This study showed that bilimbi leaves extract was able to clean the smear layer on the one-third of the apical root canal. Results: The results of the Kruskal-Wallis statistical test showed a significant difference (p<0.05) between all treatment groups. The highest average smear layer cleanliness score in the apical third of the root canals was EDTA 17%, while the lowest average smear layer cleanliness score was 5% bilimbi leaves extract. Conclusion: Bilimbi leaves extract with a concentration of 20% was considered more effective among the extract groups, and 17% EDTA was the most effective in cleaning the smear layer on one-third of the root canals.